Psychosocial work characteristic profiles and health outcomes in registered nurses at different stages of their careers: a cross-sectional study - Katri Lönnqvist; Timo Sinervo; Anu-Marja Kaihlanen; Marko Elovainio (BMC Health Services Research)
Abstract Background Individual psychosocial work characteristics have been associated with the health and well-being of registered nurses. However, it remains to be determined whether different types of psychosocial work characteristics form patterned profiles and whether the profiles are associated with registered nurses’ health and welfare at different stages of their careers. The purpose of this study was to identify latent psychosocial work characteristic profiles and examine whether the profiles are associated with a certain career stage and health outcomes. Methods This cross-sectional study was conducted with 624 early-career registered nurses and 1,016 later-career registered nurses. Data were collected using an electronic survey with internationally validated measures including the Organizational Justice Scale, the Nurse Stress Index Scale, the Job Content Questionnaire, the Team Climate Inventory, the Psychological Distress Questionnaire, the Sleep Problems Questionnaire, and the Self-Rated Health Questionnaire. Latent profile analysis was conducted to identify subgroups with similar psychosocial work characteristic profiles. Multinomial and linear regression analyses were used to examine the association between latent work characteristics profiles, stage of career, and health outcomes. Results We identified five profiles. The profiles were named based on class descriptions. The low strain/high support profile group and the moderate strain/high support profile group had statistically better self-rated health (p = < 0.001), less psychological distress (p = < 0.001) and less sleep problems (p = < 0.001) compared to the high strain/low support profile group. Conclusions Low to moderate strain, high interactional and procedural justice, and participative safety in teams form patterned profiles associated with better health in registered nurses. High strain, a lack of justice and a lack of participation safety form a risk combination pattern profile that may lead to health problems in registered nurses. Promoting procedural and interactional justice, and participation safety in teams seems efficient in enhancing the health and well-being of registered nurses. The findings indicate no significant correlation between career stages and work characteristic profiles. It is crucial to identify stressors specific for career stages and develop tailored interventions.